Virulence of Aspergillus fumigatus double mutants lacking restriction and an alkaline protease in a low-dose model of invasive pulmonary aspergillosis. - Smith, J M (1994)
To investigate the pathogenicity of Aspergillus fumigatus mutants lacking putative virulence factors, we have developed a new murine model of invasive pulmonary aspergillosis based on neutropenia, the major factor predisposing patients to this infection. Mice were treated with cyclophosphamide and inoculated by the intranasal route with 5 x 10(3) conidia, a significant reduction from inoculum levels used in previous models. Evidence for the production of the extracellular alkaline protease (Alp) in lung tissue was obtained by using a fungal transformant harboring an alp::lacZ reporter gene fusion. The pathogenicities of single mutant strains lacking either Alp or the ribotoxin restrictocin and of a double mutant strain lacking both proteins were assessed in this infection model. There were no significant differences between the mutant and the wild-type strains in terms of mortality or histological-features. Inoculations with mixtures of conidia showed that the double mutant strain is slightly less virulent than the wild-type strain. We conclude that Alp and restrictocin are not important virulence determinants in pulmonary infection.